Oxidative Stress Induced Cell Damage and Antioxidant Enzyme Response in Human Lymphocytes - Dua, Anita (International Journal of Pharmaceutical & Biological Archive, 2017)
Human lymphocytes were subjected to oxidative stress by exposing to hydrogen peroxide atconcentrations varying from 0-250Î¼M for time duration of 0-24h to evaluate cell viability. Trypan bluedye exclusion test indicated a loss of Ë‚5% cell viability on incubation with hydrogen peroxide for 24h;however MTT assay signified a decline of 55% activity after 12h or long with 200Î¼M concentration.Redox status and activities of antioxidant enzymes were examined after incubation with hydrogenperoxide up to 200Î¼M for 4h. Reduced glutathione level decreased with concentration dependent increasein lipid peroxidation, measured as MDA produced. Increase in LDH leakage from the cells withincreasing hydrogen peroxide concentration in medium indicated considerable cell membrane damage.SOD and catalase activities increased at lower concentration of 50Î¼M but at higher stress, a decline inactivities of SOD, catalase and GST was observed. GPx increased with increasing hydrogen peroxide inincubation medium. The study shows that redox status declines and cell membranes become leaky withincreasing oxidative stress. Antioxidant enzymes except GPx decrease under higher stress conditions.